The Problem with Paganism in Charity Registration in England and Wales. (3rd April 2019) - Owen, Suzanne
Abstract : Charity registration is one means by which a group can claim religious status in England and Wales. As groups must also prove their "religious" activities are for public benefit, it domesticates religion by forcing groups to conform to liberal Protestant Christian values. Examining how groups negotiate criteria for religion as defined by public bodies highlights both the problems with defining religion and how the state marginalizes groups that do not fit their criteria by denying them access to certain benefits. The problem for Pagans is they generally set out to challenge norms, not conform to them, which leaves them in a quandary when seeking registration as a religion. When the Pagan Federation failed in its applications to register as a "religion, " it was because it did not conform to the Protestant Christian model informing how religion is defined in Charity Law.